In-Track Assessment of Rail Fastenings Condition Depending on Their Deformability - A. V. Makarov (Вестник Научно-исследовательского института железнодорожного транспорта, 2015)
Monitoring of rail fastenings technical condition is necessary while trying to mitigate vehicle - track dynamic interaction as well as to reduce bedding course disconsolidation, to identify defects in the initial stage and to ensure safety of railway track opera-tion. The paper tackles the in-track identification aspect of deformed and worn out fastening elements. Identification technique is based upon comparison of structural deformations in terms of track structure loaded and unloaded conditions. Based upon thus obtained data there are discussed determination aspects of the fastenings’ structural strength dependence on their actual condition. Series of laboratory studies was conducted to identify fastening deformability dependence on the clip bolts torque values. Through the example of rail fastening ZhBR-65 inference should be drawn on the possibility to measure sleeper relative rail sinking for the purpose of in-track localization of the fastenings’ troublemaking elements with reference to 100 meter marks.